Key Service Improvements After the Introduction of an Integrated Orthogeriatric Service. (10th December 2019) - Murphy, R. P.; Reddin, C.; Murphy, E. P.; Waters, R.; Murphy, C. G.; Canavan, M.
Introduction: Models of orthogeriatric care have been shown to improve functional outcomes for patients after hip fractures and can improve compliance with best practice guidelines for hip fracture care. Methods: We evaluated improvements to key performance indicators in hip fracture care after implementation of a formal orthogeriatric service. Compliance with Irish Hip Fracture standards of care was reviewed, and additional outcomes such as length of stay, access to rehabilitation, and discharge destination were evaluated. Results: Improvements were observed in all of the hip fracture standards of care. Mean length of stay decreased from 19 to 15.5 days (mean difference 3.5 days; P < .05). A higher proportion of patients were admitted to rehabilitation (16.7% vs 7.9%, P < .05), and this happened in a timelier fashion (17.8 vs 24.8 days, P < .05). We found that less patients required convalescence post-hip fracture. Discussion: A standardized approach to integrated post-hip fracture care with orthogeriatrics has improved standards of care for patients. Conclusion: Introduction of orthogeriatric services has resulted in meaningful improvements in clinical outcomes for older people with hip fractures.